2020
DOI: 10.3855/jidc.12909
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic in resource-poor countries: challenges, experiences and opportunities in Ghana

Abstract: The novel coronavirus, SARS-CoV-2, which causes COVID-19, is seen world-wide. In developing countries, adequate health facilities and staff numbers are a concern. Ghana recorded its first 2 cases of COVID-19 on 12 March 2020. On 30 March 2020, a partial lockdown for 14 days was imposed and later extended along with other measures. By the end of the initial lockdown, 19 April 2020, an estimated 86,000 people had been traced and 68,591 tests performed. Of the 68,591 tests, there were 1,042 (1.5%) positive cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 12 publications
(12 reference statements)
1
58
0
Order By: Relevance
“…The higher risk of COVID-19 in the population with lower socioeconomic status is an important finding in developing or low-income countries. In general, the medical and human resources that provide community adaptive systems against contracting COVID-19 during the pandemic are lacking in developing or low-income countries, as reported in Vietnam and Ghana [16,17]. A previous study reported that the social insurance system in low-and middle-income countries typically covered a much smaller share of medical costs than that covered in high-income countries [18].…”
Section: Discussionmentioning
confidence: 99%
“…The higher risk of COVID-19 in the population with lower socioeconomic status is an important finding in developing or low-income countries. In general, the medical and human resources that provide community adaptive systems against contracting COVID-19 during the pandemic are lacking in developing or low-income countries, as reported in Vietnam and Ghana [16,17]. A previous study reported that the social insurance system in low-and middle-income countries typically covered a much smaller share of medical costs than that covered in high-income countries [18].…”
Section: Discussionmentioning
confidence: 99%
“…We have seen countries in Africa respond to the challenge of lack of ventilators through instigating local design with the help of universities, along with increased local production of hand sanitisers and other preventative measures including face shields and splash masks to reduce the spread of the virus as well as improve management once patients are in hospital (61,94) providing direction to others. Local production of essential preventative equipment is likely to grow across countries to reduce future shortages (61,62).…”
Section: General and Asiamentioning
confidence: 99%
“…In Ghana, the president through an Act of Parliament (Imposition of Restrictions Act [1012] of March 2020) imposed a ban on all public gatherings including restrictions on religious gatherings effective on March 15, 2020. On March 30, 2020, a three-week partial lockdown was imposed on three metropolitan areas in three regions-Ashanti, Central, and Greater Accra-which were fast becoming hot spots for the spread of the virus (Afriyie et al, 2020;Amewu et al, 2020). The ban on religious gatherings was nationwide (Ministry of Health, n.d.) and unprecedented (Boaheng, 2021).…”
Section: Introductionmentioning
confidence: 99%